ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG SAYURAN DI PASAR INDUK ANGSO DUO BARU KOTA JAMBI - edison; Saragih, Nestalida; Yanita, Mirawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
Angso Duo Baru is one of the largest wholesale markets in Jambi City and the building has been revitalized. Vegetable traders at Angso Baru Market distribute their products to earn income, but price fluctuations cause the income of vegetable traders to be uncertain. To get the maximum income, it is necessary to know what factors affect the merchant's income. This study aims to (1) describe the conditions of vegetable trading activities in the Angso Duo Baru wholesale market in Jambi City and (2) analyze the factors that affect the income of vegetable traders in the Angso Duo Baru wholesale market in Jambi City. Determination of the sample in this study is purposive with the criteria of vegetable traders who cultivate spinach, kale, and mustard greens. There were 40 traders sampled. This study uses Multiple Linear Regression (OLS). This research was conducted at the Angso Duo Baru Market in Jambi City from August 2019 to September 2019. The results showed that simultaneously working capital, education level, length of business, working hours, and the number of workers affected income. Partially the regression results show that working capital, working hours, and length of business have a significant effect on the income of vegetable traders in the Angso Duo Baru market.